2008
DOI: 10.1590/s1677-55382008000600012
|View full text |Cite
|
Sign up to set email alerts
|

Mixed incontinence: does preoperative urodynamic detrusor overactivity affect postoperative quality of life after pubovaginal sling?

Abstract: Objective: Our purpose was to determine if women with mixed urinary incontinence (MUI) and urodynamic detrusor overactivity (DO) have less improvement in urinary symptoms after pubovaginal sling surgery (PVS), compared to MUI without DO. Materials and Methods: Women with preoperative MUI symptoms prior to PVS were identified through retrospective review. DO was defined as a symptomatic 5 cm H 2 0 detrusor pressure or greater rise during urodynamics. MUI patients with and without DO before PVS were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…However, in real practice, only about 50% at most of women with MUI exhibited DO during urodynamics, which suggests that the urgency symptoms in MUI were closely linked with each other. In a preoperative urodynamic study of women with MUI, Stoffel et al reported that 42% of MUI patients had preoperative DO [25]. In our study, it was observed that 49.4% of MUI patients exhibited DO, which is similar to the report of Stoffel et al, but lower than that of Lewis et al, who insisted that 56% of SUI patients showed DO [26].…”
Section: Discussionsupporting
confidence: 85%
“…However, in real practice, only about 50% at most of women with MUI exhibited DO during urodynamics, which suggests that the urgency symptoms in MUI were closely linked with each other. In a preoperative urodynamic study of women with MUI, Stoffel et al reported that 42% of MUI patients had preoperative DO [25]. In our study, it was observed that 49.4% of MUI patients exhibited DO, which is similar to the report of Stoffel et al, but lower than that of Lewis et al, who insisted that 56% of SUI patients showed DO [26].…”
Section: Discussionsupporting
confidence: 85%
“…However, an unneglectable portion of asymptomatic patients with coexisting DO and urodynamic urinary incontinence (USI) before anti-incontinence surgery has been reported [1]. Although DO does not preclude anti-incontinence surgery and patients with DO and SUI still have improved quality of life after a sling operation, the lesser degree of symptom improvement or even the risk of persistent urgency after the surgery still bothers patients with coexisting DO and mixed urinary incontinence [2,3]. Hence, identifying DO has an essential role in the preoperative evaluation [4].…”
Section: Introductionmentioning
confidence: 99%
“…The demonstration of detrusor overactivity in women with mixed incontinence has been reported to be between 11-56%. [46][47][48] Other publications have looked more specifically at the urodynamics of patients with urge or stresspredominant MUI.…”
Section: Should the Predominant Symptom Be Treated First?mentioning
confidence: 99%